Analisis Keterampilan Menulis Puisi dengan Menggunakan Metode Quantum Learning: Analysis of poetry writing skills using the quantum learning method - Hidayatusholikah, Ning; Hasanudin, Cahyo; Rohman, Nur (Journal of Literature and Education, 2023)
This study aims to determine poetry written by students of class X-B MA Sunan Bonang Parengan Tuban, Indonesia in learning to write poetry using the quantum learning method. This research is a case study research with 11 students as subjects. Of the 11 students, the researcher took 5 students to be interviewed on the grounds that they had good poetry writing skills according to the indicators. Data collection techniques using observation, test methods, interviews, and documentation. Data was validated using source triangulation and method triangulation. The data analysis technique uses the content analysis method starting from (1) data reduction, (2) data presentation, and (3) drawing conclusions. The results showed that poetry written by students of class X-B MA Sunan Bonang Parengan Tuban, Indonesia already referred to the structure of poetry according to Waluyo. The conclusion in this study is that the quantum learning method is very appropriate for learning. This quantum learning method can make students more active and creative in taking lessons and making poetry.